A novel observation of Widmanstätten ferrite and pearlite by thermo-mechanical processing of interstitial-free steel. Issue 15 (18th November 2022) - Sinha, M.; Yadav, S.; Ghosh, S.
ABSTRACT: In the present work, interstitial-free steel is rapidly cooled from the austenitic state, followed by isothermal holding at 630°C for 5 minutes in a thermo-mechanical simulator (Gleeble 3800®). The heat-treatment provides massive ferrite, Widmanstätten ferrite and pearlite, as the triplex-phase mixture. Massive ferrite, as the early decomposed product of austenite, arises by rapid cooling. Subsequent formation of Widmanstätten ferrite and pearlite during the isothermal holding is elusive in steel. The phase transformations account for a dramatic improvement in tensile strength by two-fold with a negligible reduction in elongation. Morphologically, massive ferrite is granular and contains recovered sub-grain boundaries inside the phase. The pearlite nucleates within a lath-shaped grain, unconventionally. Due to the low-temperature phase transformation (630°C) and a ppm level carbon in the alloy, the observed pearlitic structure is either underdeveloped or fragmented, which promotes cracks against the stronger Widmanstätten ferrite at an advancing front of the crack tip.